A Critical Review on the Analysis of Metal Soaps in Oil Paintings. Issue 9 (17th September 2021) - Izzo, Francesca Caterina; Kratter, Matilde; Nevin, Austin; Zendri, Elisabetta
Abstract: Up to 70 % of the oil paintings conserved in collections present metal soaps, which result from the chemical reaction between metal ions present in the painted layers and free fatty acids from the lipidic binders. In recent decades, conservators and conservation scientists have been systematically identifying various and frequent conservation problems that can be linked to the formation of metal soaps. It is also increasingly recognized that metal soap formation may not compromise the integrity of paint so there is a need for careful assessment of the implications of metal soaps for conservation. This review aims to critically assess scientific literature related to commonly adopted analytical techniques for the analysis of metal soaps in oil paintings. A comparison of different analytical methods is provided, highlighting advantages associated with each, as well as limitations identified through the analysis of reference materials and applications to the analysis of samples from historical paintings. Abstract : Conservation and Heritage scientists frequently face challenging issues related to metal soaps phenomena in oil paint systems. This review provides a critical overview of analytical techniques available for the identification, localisation and study of the presence of metal soaps. Advantages and disadvantages of each technique are discussed and the comparison between data collected from ad hoc and real painting samples is reported.